Design and Implementation of Network Security Systems on Virtualized Networks - Syam, Akmal Baharuddin; Rahman, Rakhmadi (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
This report, entitled